A gero-informatics tool to enhance the care of hospitalized older adults with cognitive impairment - Malaz Boustani (Dove Medical Press, 2007)
Malaz Boustani1, Stephanie Munger1, Robin Beck2, Noll Campbell3, Michael Weiner11Indiana University Center for Aging Research, Regenstrief Institute, Inc, Indianapolis, IN, USA; 2Indiana University School of Medicine, Indianapolis, IN, USA; 3Wishard Health Services, Indianapolis, IN, USAAbstract: Approximately 50% of hospitalized elders have cognitive impairment (CI) that increases their vulnerability to hospital-acquired complications. Matching geriatric evaluation and recommendations to the true pace of hospital care may improve the care of elders in general, in particular those with CI. Integrating information technology into geriatric services (gero-informatics) might allow reduction of the time to implementation of geriatric recommendations and prevent the initiation of potentially harmful medications and procedures during the critical first 48 hours of hospitalization. This paper reviews our local gero-informatics early experience of developing a computerized decision support system (CDSS) to enhance hospital care for elders with CI by reducing inappropriate use of anticholinergic medications, urinary catheters, and physical restraints.Keywords: gero-informatics, cognitive impairment, hospital, decision support